Anti-Cytomegalovirus Activity in Human Milk and Colostrum From Mothers of Preterm Infants. Issue 5 (November 2018) - Donalisio, Manuela; Rittà, Massimo; Tonetto, Paola; Civra, Andrea; Coscia, Alessandra; Giribaldi, Marzia; Cavallarin, Laura; Moro, Guido E.; Bertino, Enrico; Lembo, David
ABSTRACT: Objectives: This study aimed to investigate the anti-human cytomegalovirus (CMV) activity of milk from seropositive and seronegative mothers of preterm infants and to analyze its changes throughout the different stages of lactation and after Holder pasteurization, a procedure adopted by donor human milk banks. Methods: Eighteen mothers of preterm infants were enrolled in the study. Colostrum, transitional milk, and mature milk samples were collected and tested for anti-CMV activity. Depletion of immunoglobulins A from milk samples was carried out by jacalin resin. Pools of milk samples were pasteurized according to Holder technique. Results: All samples were endowed with anti-CMV activity, although to a different extent. In CMV IgG-positive mothers, colostra were significantly more active than the transitional milk and mature milk samples. Moreover, they were more potent than colostra from seronegative mothers. Immunoglobulins A depletion in colostra from IgG-positive mothers resulted in a partial loss of anti-CMV activity. Holder pasteurization significantly reduced the antiviral activity. Conclusions: Human milk is endowed with anti-CMV activity and its potency may vary depending on the stage of lactation and the serological status of the mother. This biological property could partially neutralize CMV particles excreted in the milk of CMV IgG-positive mothers thus reducing the risk of transmitting infectious viruses to the infant. Abstract : Supplemental Digital Content is available in the text